2013
DOI: 10.1016/j.febslet.2012.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Rab proteins to peroxisomes: A proteomics and immunofluorescence study

Abstract: a b s t r a c tA proteomics screen was initiated to identify Rab proteins regulating transport to and away from peroxisomes. Mass spectrometry-based protein correlation profiling of rat liver organelles and immunofluorescence analysis of the peroxisome candidate Rab proteins revealed Rab6, Rab10, Rab14 and Rab18 to associate with the peroxisomal membrane. While Rab14 localized to peroxisomes predominantly in its dominant-active form, other Rab proteins associated with peroxisomes in both their GTP-and GDP-boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…RAB14 belongs to the large RAB family of low molecular mass GTPases that are involved in intracellular membrane trafficking [47]. In our previous study, RAB14 has been identified as a functional target of miR-451 in NSCLC, but the expression of RAB14 showed no difference between docetaxel-resistant and parental LAD cells (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…RAB14 belongs to the large RAB family of low molecular mass GTPases that are involved in intracellular membrane trafficking [47]. In our previous study, RAB14 has been identified as a functional target of miR-451 in NSCLC, but the expression of RAB14 showed no difference between docetaxel-resistant and parental LAD cells (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…The lack of a peroxisomal localization of RabGAP22-GFP in unstressed plants (Figure 2C) suggests that a specific re-localization of RabGAP22 to peroxisomes takes place under biotic stress conditions, here exemplified in response to V. longisporum . Changes in subcellular localization and activity of GTPases, GAPs and GEFs frequently occur in response to changes in the GTP/GDP-bound state [35] and also in response to phosphorylation of individual residues in these molecules [36]. The rice Rab protein OsRab11 is characterized both for regulating vesicular trafficking between the trans-Golgi network and vacuole [37], [38] and for interaction with the peroxisomal protein OsOPR8 [39].…”
Section: Resultsmentioning
confidence: 99%
“…A complete set of proteins essential for heterotypic fusion reactions requires N-ethylmaleimidesensitive factor (NSF; LDBPK_200820), and soluble NSF attachment protein receptors (SNAREs; LDBPK_352760 and LDBPK_070570) (Lam et al, 2010) were also found in glycosomal fraction. Several Rab proteins, ras-like small GTPase, and GTP binding proteins that are essential regulators of vesicle trafficking (Gronemeyer et al, 2013) were also found in the proteomic analysis of glycosomes. Chaperone T-complex (LDBPK_321060) and small Rab-GTPases proteins known to interact with peroxin-7, were found in the glycosomal fraction.…”
Section: Peroxisome Biogenesis Proteinsmentioning
confidence: 97%